Gluteus Maximus Muscle Flap in Tongue in Groove and Wrap Around Pattern for Refractory CSF Leakage in Extradural Cyst Patient - Park, Kyong Chan; Lee, Jun Ho; Shim, Jae Jun; Lee, Hyun Ju; Choi, Hwan Jun (Archives of Plastic Surgery, 2022)
Spinal extradural arachnoid cyst (SEAC) is a rare disease and has surgical challenges because of the critical surrounding anatomy. We describe the rare case of a 58-year-old woman who underwent extradural cyst total excision with dural repair and presented with refractory cerebrospinal fluid (CSF) leakage even though two consecutive surgeries including dural defect re-repair and lumbar-peritoneal shunt were performed. The authors covered the sacral defect using bilateral gluteus maximus muscle flap in tongue in groove and wrap around pattern for protection of visible sacral nerve roots and blockage of CSF leakage point. With the flap coverage, the disappearance of cyst and fluid collection was confirmed in the postoperative radiological finding, and the clinical symptoms were significantly improved. By protecting the sacral nerve roots and covering the base of sacral defect, we can minimize the risk of complication and resolve the refractory fluid collection. Our results suggest that the gluteus muscle flap can be a safe and effective option for sacral defect and CSF leakage in extradural cyst or other conditions.
Keywords: tongue in groove and wrap around pattern; gluteus maximus muscle flap; extradural cyst; cerebrospinal fluid; sacral defect